2022
DOI: 10.1021/acs.langmuir.2c00508
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis and Solvothermal Synthesis for Carbon Dots: Role of Purification and Molecular Fluorophores

Abstract: Over the last decade, the interest in carbon dots, graphene dots, or similar carbon-based nanoparticles has increased considerably. This interest is based on potentially high fluorescent quantum yields, controllable excitation-dependent emission, low toxicity, and convenient reaction conditions. Carbon dots are often seen as a promising alternative to classical semiconductor quantum dots that are typically made from toxic semiconductor materials. Surprisingly, aspects like the atomic structure, composition, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…85 Then, Rogach's group proved that citrazinic acid is the main fluorophore responsible for the blue fluorescence of CDs prepared from CA and urea (recent reports also indicate the presence of oligomeric ureas, 5-oxopyrrolidine-3-carboxylic acid and other blue PL emitting species in these materials). [86][87][88][89] After careful evaluation of the optical properties of CDs obtained at different reaction times, it was concluded that at the initial stages of CD synthesis molecular fluorophores dominate their absorption and fluorescence characteristics, while for CDs prepared at longer reaction times more and more pronounced contribution of carbonized species becomes apparent (Fig. 2).…”
Section: Cbmfs In Blue-emitting Cdsmentioning
confidence: 99%
“…85 Then, Rogach's group proved that citrazinic acid is the main fluorophore responsible for the blue fluorescence of CDs prepared from CA and urea (recent reports also indicate the presence of oligomeric ureas, 5-oxopyrrolidine-3-carboxylic acid and other blue PL emitting species in these materials). [86][87][88][89] After careful evaluation of the optical properties of CDs obtained at different reaction times, it was concluded that at the initial stages of CD synthesis molecular fluorophores dominate their absorption and fluorescence characteristics, while for CDs prepared at longer reaction times more and more pronounced contribution of carbonized species becomes apparent (Fig. 2).…”
Section: Cbmfs In Blue-emitting Cdsmentioning
confidence: 99%
“…However, it is now clearly emerging that this is not sufficient for many CDs preparations and a combination of alternative purification techniques (i.e., gel electrophoresis and chromatography) should be employed more routinely. [ 7–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now clearly emerging that this is not sufficient for many CDs preparations and a combination of alternative purification techniques (i.e., gel electrophoresis and chromatography) should be employed more routinely. [7][8][9][10] Here, we aim at employing the technology of CDs to develop new multifunctional materials as contrast agents (CAs) in magnetic resonance imaging (MRI). As well known, most of CAs currently used in MR medical imaging, are gadolinium (III) (Gd) based complexes (Gadolinium-based Contrast Agents, GDCAs), whilst alternative systems, such as iron oxide and manganese compounds are still to be confirmed for a wide use in clinics.…”
Section: Introductionmentioning
confidence: 99%
“…CDs are prepared using either top-down or bottom-up methods including laser ablation [ 20 ], ultrasonication [ 21 , 22 ], arc discharge [ 23 ], simple heating [ 24 ], and solvothermal [ 25 , 26 ]. Chemical precursors such as acid derivatives, thiourea derivatives, and carbohydrates were employed to prepare CDs [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%